Can you multiply to infinity?

Calculus Level 3

Evaluate the given expression for Q:

n = 2 ( 1 1 n 2 ) \displaystyle\prod _{ n=2 }^{ \infty }{ (1-\frac { 1 }{ { n }^{ 2 } } ) } = Q \textbf{Q}

If Q \textbf{Q} can be represented as a b \frac { a }{ b } , where a \textbf{a} and b \textbf{b} are coprime integers, then what is a + b a+b ?


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mehul Chaturvedi
Jan 27, 2015

The product of the first N 1 N - 1 terms can be written as n = 2 N n 2 1 n 2 = n = 2 N ( n 1 ) ( n + 1 ) n n \displaystyle\prod_{n=2}^{N} \dfrac{n^{2} - 1}{n^{2}} = \prod_{n=2}^{N} \dfrac{(n - 1)(n + 1)}{n*n} .

Now we'll get a series like this

( 1 ) × ( 3 ) 2 × 2 × ( 2 ) × ( 4 ) 3 × 3 × ( 3 ) × ( 4 ) 4 × 4 . . . . . . . . \dfrac{(1)\times(3)}{2\times 2}\times\dfrac{(2)\times(4)}{3\times 3}\times\dfrac{(3)\times(4)}{4\times 4}........ and so on

Now all the 'middle' terms cancel, leaving us with the product

1 2 N + 1 N \dfrac{1}{2} * \dfrac{N+1}{N} , which as N N \rightarrow \infty goes to 1 2 \dfrac{1}{2} . Thus a + b = 1 + 2 = 3 a + b = 1 + 2 = \boxed{\huge\color{royalblue}{{3}}} .

Again, a formal way to represent this is to demonstrate the index shifting in the product notation as:

Q = n = 2 ( n 1 ) ( n + 1 ) n 2 = ( n = 2 ( n 1 ) n ) ( n = 3 n ( n 1 ) ) Q=\prod_{n=2}^\infty \dfrac{(n-1)(n+1)}{n^2} =\left(\prod_{n=2}^\infty \dfrac{(n-1)}{n}\right)\left(\prod_{n=3}^\infty \dfrac{n}{(n-1)}\right)

Q = 1 2 n = 3 ( ( n 1 ) n n ( n 1 ) ) = 1 2 n = 3 ( 1 ) = 1 2 \implies Q=\dfrac{1}{2}\cdot \prod_{n=3}^\infty \left(\dfrac{(n-1)}{n}\cdot \dfrac{n}{(n-1)}\right) = \dfrac{1}{2}\cdot \prod_{n=3}^\infty\left(1\right) = \dfrac{1}{2}

Prasun Biswas - 6 years, 4 months ago

The product of the first N 1 N - 1 terms can be written as

n = 2 N n 2 1 n 2 = n = 2 N ( n 1 ) ( n + 1 ) n × n \displaystyle\prod_{n=2}^{N} \dfrac{n^{2} - 1}{n^{2}} = \prod_{n=2}^{N} \dfrac{(n - 1)(n + 1)}{n\times n} .

Written in this form it is clear that we have a telescoping product, where all the 'middle' terms cancel, leaving us with the product

1 2 N + 1 N \dfrac{1}{2} * \dfrac{N+1}{N} , which as N N \rightarrow \infty goes to 1 2 \dfrac{1}{2} .

Thus a + b = 1 + 2 = 3 a + b = 1 + 2 = \boxed{3} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...